Answer:
[tex]\frac{x}{2} = \frac{(y - 5)}{5}[/tex]
Step-by-step explanation:
We are given the equation [tex]\frac{(x + 2)}{2} = \frac{y}{5}[/tex] .......... (1) and we have to find the equivalent expression for above expression from options.
Now, the expression can be rearranged as
[tex]\frac{(x + 2)}{2} = \frac{y}{5}[/tex]
⇒ [tex](\frac{x}{2} + 1) = \frac{y}{5}[/tex]
⇒ [tex]\frac{x}{2} = \frac{y}{5} - 1[/tex]
⇒ [tex]\frac{x}{2} = \frac{(y - 5)}{5}[/tex]
Therefore, this [tex]\frac{x}{2} = \frac{(y - 5)}{5}[/tex] will be true for the expression (1). (Answer)